Vpliv uporabe IKT in izkustvenega učenja na mnenje učencev o naravoslovnem dnevu na morski obali - Cotič, Nastja; Zuljan, Darjo; Plazar, Janja (Revija za elementarno izobraževanje, 2019)
The Influence of ICT and Experiential Learning on Student's Attitudes towards Science Lessons at the Seashore. The article analyses the translation of nominal address forms from English to Slovene. The goal of the research was to determine, with the help of a linguistic analysis of subtitles in the films, the impact of sociolinguistic factors (gender, age and social status were chosen for the purpose of this research) on the translation of nominal address forms. The empirical part is based on a comparison of the original English speech in two films, Hue and Cry and Indiscreet, and their Slovene subtitles.
Keywords: ICT; experiential learning; science day; seashore; attitude towards science education